Protective and detrimental effects of sodium sulfide and hydrogen sulfide in murine ventilator-induced lung injury - Francis, Roland C. E.; Vaporidi, Katerina; Bloch, Kenneth D.; Ichinose, Fumito; Zapol, Warren M. (Anesthesiology, 2011)
Background: The antiinflammatory effects of hydrogen sulfide (H 2S) and sodium sulfide (Na2S) treatment may prevent acute lung injury induced by high tidal volume (HVT) ventilation. However, lung protection may be limited by direct pulmonary toxicity associated with H 2S inhalation. Therefore, the authors tested whether the inhalation of H2S or intravascular Na2S treatment can protect against ventilator-induced lung injury in mice. Methods: Anesthetized mice continuously inhaled 0, 1, 5, or 60 ppm H2S or received a single bolus infusion of Na2S (0.55 mg/kg) or vehicle and were then subjected to HVT (40 ml/kg) ventilation lasting 4 h (n = 4-8 per group). RESULTS:: HVT ventilation increased the concentrations of protein and interleukin-6 in bronchoalveolar lavage fluid, contributing to reduced respiratory compliance and impaired arterial oxygenation, and caused death from lung injury and pulmonary edema. Inhalation of 1 or 5 ppm H2S during HVT ventilation did not alter lung injury, but inhalation of 60 ppm H2S accelerated the development of ventilator-induced lung injury and enhanced the pulmonary expression of the chemoattractant CXCL-2 and the leukocyte adhesion molecules CD11b and L-selectin. In contrast, pretreatment with Na2S attenuated the expression of CXCL-2 and CD11b during HVT ventilation and reduced pulmonary edema. Moreover, Na2S enhanced the pulmonary expression of Nrf2-dependent antioxidant genes (NQO1, GPX2, and GST-A4) and prevented oxidative stress-induced depletion of glutathione in lung tissue. Conclusions: The data suggest that systemic intravascular treatment with Na2S represents a novel therapeutic strategy to prevent both ventilator-induced lung injury and pulmonary glutathione depletion by activating Nrf2-dependent antioxidant gene transcription. © 2011 the American Society of Anesthesiologists, Inc. Lippincott Williams & Wilkins. Anesthesiology.
CRIS-Team Scopus Importer:2022-11-17